Kristus Adalah Kegenapan Hukum Taurat - Harvijanto, Andri (JURNAL ILUMINASI, 2023)
For Christ is the end of the law. By the "law" here, is not meant the ceremonial law, of which, indeed, they were all very zealous, and of which Christ also was the end in many respects. He was the final cause of it, or that for the sake of which it was; it had not been given had it not been for him; all its institutions, ordinances, and sacrifices, were on his account: they were all shadows of him, and he the body and substance of them. Christ was the end or mark and scope at which they all aimed; every type looked to him, and every offering directed the worshipper to him; he was the terminus of it, to whom it was to reach, and beyond whom it was not to go; it was a schoolmaster for instruction and direction until Christ came, and no longer. He was the fulfilling end of it, everything in it had its accomplishment in him; and then lastly, he put an end to it, he disannulled it because of its after weakness and unprofitableness; he blotted out this hand writing of ordinances, and entirely abolished this law of commandments; but then Christ was not the end of this law for righteousness. Christ's obedience to it is no part of justifying righteousness, especially not to everyone that believes.